Improving EFL Learning Outcomes by Using Interactive Multimedia Approach - Nabung, Adrianus (Universitas Muhammadiyah Metro, 2023)
The dynamic lingkage of interactive multimedia approach and learning styles can effect the EFL students’ learning outcomes. In this present research, the combination of text, video, audio, and kinesthetic will be effective. With the aim of analyzing the effect of using interactive multimedia and learning styles on students' English learning outcomes, this research was conducted. This research approach is a quantitative approach with a quasi-experimental type of research. The subjects of this study were the students of vocational schools in Manggarai, NTT-East Indonesia. Sampling used purposive cluster by considering the characteristics of the school and obtained two sample schools, namely SMK Swakarsa as the control group and SMK Karya as the experimental group. The total number of students involved is 65 people. Research data were collected through learning style identification tests and student learning outcomes tests.